How Important Is the Family? Evidence from Sibling Correlations in Permanent Earnings in the USA, Germany, and Denmark - Daniel D. Schnitzlein (Journal of Population Economics, 2014)
This paper is the first to analyze the impact of family background on permanent earnings based on sibling correlations in Germany and to provide a cross-country comparison of Germany, Denmark, and USA. The main findings are that family and community background has a stronger influence on permanent earnings in Germany than in Denmark, and a comparable influence is found in USA. This holds true for both male and female siblings. A deeper analysis of Germany shows that family background also plays an important role in explaining variations in family income, wages, education, and risk attitudes.
Additional information: The final publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s00148-013-0468-6
Keywords: D1; D3; J62; 330; Sibling correlations; Intergenerational mobility; REML; Germany; SOEP; Soziale Beziehungen; Soziale Gruppe; Soziales Netzwerk; Zufriedenheit; Einkommen; Lohn; Familie; Vergleich; Dänemark; Deutschland; USA